Desertification and Changes in the Geomorphic Processes - Mensching, H G; Akhtar, M (Annals of Arid Zone, 2025)
Desertification is land degradation in arid, semi-arid and dry sub-humid zones arising from various factors, including climatic variation and human impact (UNEP, 1993). Desertification can have an immense impact on the semi-arid geomorphic system. This implies to nearly-all processes of this system, whether fluvial or aeolian. A short but systematic delineation of desertification in different relief units, and examples from some ofthe investigated drylands of the world are the principal objectives of this contribution. Although changes in geomorphic processes are only a subset of the entire phenomena of desertification a modification within the complex process combinations can have important consequences for the natural resources of drylands. Desertification processes cause an aridifiction of the ecosystem, affecting the vegetation cover, the soils and the water balance.